2021
DOI: 10.21203/rs.3.rs-135081/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic Analysis of The Poultry Red Mite, Dermanyssus Gallinae, Across All Stages of The Lifecycle.

Abstract: Background: The blood feeding poultry red mite (PRM), Dermanyssus gallinae, causes substantial economic damage to the egg laying industry worldwide, and is serious welfare concern for laying hens and poultry house workers. In this study we have investigated the temporal gene expression across the 6 stages/sexes (egg, larvae, protonymph and deutonymph, adult male and adult female) of this neglected parasite in order to understand the temporal expression associated with development, parasitic lifestyle, reproduc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Previous genotyping of several successive batches of dozens of mites randomly sampled at different locations and times in farm DIN showed that the poultry red mites that develop in this farm only belong to D. gallinae s.s. (more precisely, 100% of the genotyped individuals carried haplotypes of the haplogroup C, very common in French layer farms) 27 . Selection of mites to be inoculated into the mesocosms was performed under a stereomicroscope, retaining the largest mites to form a 100% female inoculum as in Bartley et al 28 . Only live and active mites were collected, using a P1000 filter pipette tip connected to a vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
“…Previous genotyping of several successive batches of dozens of mites randomly sampled at different locations and times in farm DIN showed that the poultry red mites that develop in this farm only belong to D. gallinae s.s. (more precisely, 100% of the genotyped individuals carried haplotypes of the haplogroup C, very common in French layer farms) 27 . Selection of mites to be inoculated into the mesocosms was performed under a stereomicroscope, retaining the largest mites to form a 100% female inoculum as in Bartley et al 28 . Only live and active mites were collected, using a P1000 filter pipette tip connected to a vacuum pump.…”
Section: Methodsmentioning
confidence: 99%